North American winter‐spring storms: Modeling investigation on tropical Pacific sea surface temperature impacts. Issue 19 (3rd October 2013) - Basu, Soumik; Zhang, Xiangdong; Polyakov, Igor; Bhatt, Uma S.
<x xml:space="preserve">Abstract</x> [1] An increased frequency and intensity of winter and spring storms have recently manifested over a broad area of North America—along the east coast of the U.S. especially, though global mean storm tracks are suggested to shift northward. To understand these changes, we have conducted atmospheric model experiments, examining the response of North American storm activity to the elevated tropical Pacific sea surface temperature (SST) associated with El Niño. The results indicate that, when tropical Pacific SST increases, there are more numerous intense storms over southwestern, southeastern, and northwestern North America, but fewer weaker storms over the northeast. Transient eddy analysis of the general circulation demonstrates consistent changes, suggesting systematic changes from large‐scale general circulation to synoptic‐scale storms. These changes can be attributed to enhanced lower tropospheric baroclinicity, to which the southward shift and an intensification of extratropical jet streams make a major contribution.